RELIGIUS CULTURE SEBAGAI FONDASI PEMBENTUKAN DISIPLIN SISWA DALAM PEMBELAJARAN PAI DI SEKOLAH DASAR NEGERI DUKUHSARI SUKOREJO - Rizkiyah Fitri Nurhidayah; Ali Mohtarom (STKIP Subang, 2026)
This study aims to describe and analyze the forms of religious culture implementation in Islamic Religious Education (PAI) learning and its role in shaping and strengthening student discipline at SDN Dukuhsari Sukorejo. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation. The findings reveal that religious culture at SDN Dukuhsari Sukorejo is implemented through three main forms: verbal-ritual habituation (recitation of Asmaul Husna, sholawat, and prayers), worship habituation (Dhuha prayer and Quranic memorization), and attitude and character habituation (salam culture, polite dress, and respectful behavior). These activities are systematically integrated into every stage of PAI learning. The results show that religious culture contributes significantly to the formation of student discipline through two mechanisms: repeated habituation and internalization of religious values. Indicators of improved discipline include increased punctuality, reduced rule violations, greater active participation in learning, and growing mutual respect among students. This study concludes that religious culture, when consistently implemented with teacher exemplary conduct and committed leadership, can form internal discipline that is more durable than discipline enforced by external rules and sanctions.